Effect of intercropped and micro nutrient fertilizers for Cucurbita pepo L. And Cucumis sativus L. On water productivity and yield under drip irrigation system: Effect of Intercropped and Micro Nutrient Fertilizers For Cucurbita pepo L. and Cucumis sativus L. on Water Productivity and Yield Under Drip Irrigation System - Ati, Alaa Salih; Hassan, Kadhim Dealy; Naser, Kadhim Makee (Journal of Kerbala for Agricultural Sciences, 2018)
ABSTRACT: Field experiment was carried out during spring season of 2017 in the field of Agricultural Collage- University of Baghdad/ Al - Jadriya., Iraq in silt loam calcareous soil to study the effect of micronutrients and water amount applied to intercropped Cucurbita pepo and Cucumis sativus on yield and water use efficiency. Cucurbita pepo (Pumpkin) (synthetic cv. US, Agriseed, Fadwa) and Cucumis sativus (cucumber) (synthetic cv. Kazear) were planted monocropping and a strip intercropped. The experiment was a Split Plot Design arranged in RCBD with three replications. micronutrients treatment represents the main plot and intercropping system treatment as sub plot. Micronutrients treatments included application of 3 rates 0, 150 and 250 g 1000 m-2. Monocropping for Pumpkin and cucumber were planted one line in treatments unit, while Intercropping for Pumpkin and cucumber were planted two line for any one in treatment units. All plots were irrigated with river water (ECi =1.45 dS m-1), and irrigation was imposed at 35% depletion of available water using drip irrigation system. Results indicated that number of irrigations were 18,19 and 17 for monocropping of Cucurbita pepo, Cucumis sativus and intercropping irrigation systems consuming 410 and 425 and 440 mm for the three treatments, respectively. All growth and yield parameters were no significantly at or/and at monocropping compared to intercropping. The interactions effect between the amount of micronutrient and water on fruits yield indicated that the best two treatments were 250 g 1000 m-2 with mono or/and intercropping (the best overall treatment and no significant with 150 g 1000 m-2), and Values of IWUE for intercropping are almost more than monocropping